(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article reveals the history of creation of the novel «Hard times» written by M. Auezov. It characterizes the main features of the author’s early prose poetics, and describes the principles of creating images, particularly, the characters of this novel. In this article particular attention is paid to the chronological aspect, that is, to the period of time when the novel was created. Ethno-cultural components related to the national colouring and national picture of the world are the foundation of the creative method of Mukhtar Auezov in the novel «Hard times.» It should be noted that the research topic of the article is important due to the fact that the novel «Hard times» is a historical work about the national liberation movement of the Kazakh people in the early 20th century. The history of our people in the literary reflection is an important aspect of the research to date.